Ownership concentration, owner identity and technological innovation propensity - Safi Ullah Khan; Mohammad Faisal Rizwan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
This paper examines, from the perspectives of the agency-theoretic approach, how ownership concentration impacts technological innovation. We conduct this analysis by allowing the effect to vary according to the identity of the main shareholder and test several hypotheses by employing survey data for 21 developing countries. Initial evidence suggests that concentrated corporate ownership is negatively related to technological innovation propensity, a result contrary to the 'agency cost minimization effect' of ownership concentration. Disentangling this negative correlation, we show that, where the largest shareholder is a family, firms are likely to have lower technological innovation propensity than firms with a foreign or a domestically-owned corporate group as the main shareholder. Further uncovering the negative effect for family-owned businesses, we show that risk aversion, induced by the lack of corporate diversification, negatively affects technological innovation propensity. Finally, the impact of family firms on innovation propensity appears to be negative only for radical innovation, and family and non-family firms have no differential innovation propensity for incremental innovation. In sum, this paper provides new evidence on innovation processes in family firms by investigating the moderating role of corporate diversification on the technological innovation propensity. We find that corporate diversification moderates the relationship between family involvement in ownership and technological innovation propensity.
Keywords: 330; technological innovation; concentrated ownership; radical and incrementalinnovation; product and process innovation; corporate diversification